The use of molybdenum oxide nanoparticles for production of free isotope Mo-99 - Dikiy, N.P.; Dovbnya, A.N.; Krasnoselsky, N.V.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Uvarov, V.L.; Fedorets, I.D. (Вопросы атомной науки и техники, 2015)
The possibility of photonuclear production of ⁹⁹Mo medical radioisotopes using recoil nuclei of nanoparticles MoO₃ from reaction ¹⁰⁰Mo(γ,n)⁹⁹Mo was investigated. (γ,n)-reaction does not be accompanied by change in nuclear charge. Therefore, the enrichment of radioactive isotopes is being carried out using methods based on the effect of Szilard-Chalmers. The highest concentration of ⁹⁹Mo is required for manufacturing of ⁹⁹mTc-⁹⁹Mo generators. These generators will promote successful using ⁹⁹mTc in nuclear medicine. MoO₃ nanoparticles of size 13…80 nm were placed in isopropyl alcohol and ethylene glycol. The colloidal solution of MoO₃ is achieved by sonication. The colloidal solution of nanoparticles of MoO₃ was irradiated by bremsstrahlung with Emax = 12.5 MeV. The recoil nuclei of ⁹⁹Mo were separated by means of diantipyrylmethane in sulfuric acid solution. Yield of ⁹⁹Mo from extractable phase amounted ~ 4%, in consequence of the high density of MoO₃ nanoparticles in a colloidal solution. Була досліджена можливість фотоядерного виробництва медичного радіоізотопу ⁹⁹Mo при використанні ядер віддачі з наночастинок MoO₃ з реакції ¹⁰⁰Mo(γ,n)⁹⁹Mo. (γ,n)-реакції не супроводжуються зміною заряду ядра, тому збагачення радіоактивних ізотопів проводилося з використанням методів, заснованих на ефекті Сциларда-Чалмерса. Висока концентрація ⁹⁹Mo потрібно для виготовлення генераторів ⁹⁹мТс-⁹⁹Mo. Ці генератори дозволять успішно використовувати ⁹⁹мТс в ядерній медицині. MoO₃ − наночастинки розміром 13…80 нм були поміщені в ізопропіловий спирт і етиленгліколь. Колоїдний розчин MoO₃ досягався обробкою ультразвуком. Колоїдний розчин наночастинок MoO₃ був опромінений гальмівним ви-промінюванням з Емакс= 12,5 МеВ. Ядра віддачі ⁹⁹Mo були виділені з сірчанокислого розчину з використанням діантіпірілметана. Вихід ⁹⁹Mo в екстрагуєму фазу склав ~ 4%, що зумовлено високою щільністю наночастинок молібдену в колоїдному розчині. Была исследована возможность фотоядерного производства медицинского радиоизотопа ⁹⁹Mo при использовании ядер отдачи из наночастиц MoO₃ по реакции ¹⁰⁰Mo(γ,n)⁹⁹Mo. (γ,n)-реакции не сопровождаются изменением заряда ядра, поэтому обогащение радиоактивных изотопов проводилось с использованием методов, основанных на эффекте Сциларда-Чалмерса. Высокая концентрация ⁹⁹Mo требуется для изготовления генераторов ⁹⁹мТс-⁹⁹Mo. Эти генераторы позволят успешно использовать ⁹⁹мТс в ядерной медицине. MoO₃ − наночастицы размером 13…80 нм были помещены в изопропиловый спирт и этиленгликоль. Коллоидный раствор MoO₃ достигался обработкой ультразвуком. Коллоидный раствор наночастиц MoO₃ был облучен тормозным излучением с Емакс = 12,5 МэВ. Ядра отдачи ⁹⁹Mo были выделены из сернокислого раствора с использованием диантипирилметана. Выход 99Mo в экстрагируемую фазу составил ~ 4%, что обусловлено высокой плотностью наночастиц молибдена в коллоидном растворе.